Factors Influencing Pulmonary Tuberculosis Treatment Adherence among Farmers in Western Muna District 2022 - Habriani; La Ode Muhamad Sety; Adius Kusnan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Tuberculosis (TB) is caused by bacteria (Mycobacterium tuberculosis) which most commonly attacks the lungs. This disease can spread easily from person to person through the air, but can be cured or prevented. The purpose of this study was to analyze the factors that influence pulmonary TB treatment adherence to farmers in West Muna Regency in 2022. This research is quantitative using descriptive research methods. The population in this study amounted to 40 people. The sample in this study is the total population of 40 people. Data analysis used univariate and bivariate analysis with the help of SPSS 20.0. The results of testing the effect of motivation, family support on adherence to treatment of pulmonary TB in farmers are as follows: the effect of motivation on adherence to treatment has a P-Value of 0.004 <0.05, the effect of family support on adherence to treatment has a P-Value of 0.305 ≥0, 05. The results showed that there was an influence between the motivation of pulmonary TB patients on adherence to pulmonary TB treatment in farmers. While there is no effect between family support on adherence to pulmonary TB treatment in farmers